Pendekatan TEACCH dalam Meningkatkan Kemandirian Belajar Anak dengan ASD: Tinjauan Literatur Sistematis - Lukmanul Hakim; Muh. Hasani; Muh. Rusli Umaini (PT. Penerbit Tiga Mutiara, 2025)
Individuals with Autism Spectrum Disorder (ASD) commonly face challenges in independent learning and mastery of functional skills due to deficits in communication, social interaction, as well as repetitive and restricted behaviors. The Treatment and Education of Autistic and Related Communication Handicapped Children (TEACCH) approach was developed to address the specific educational needs of this population through structured, visually based, and strengths-based learning. Although the effectiveness of TEACCH has been widely reported globally, studies systematically examining its application within the Indonesian educational context remain limited. This study aims to critically evaluate the effectiveness of the TEACCH approach in enhancing independent learning among children with ASD in Indonesia. Using a systematic review method based on the PRISMA protocol, 15 scholarly articles published between 2017 and 2024 were thematically analyzed to identify TEACCH’s contribution to increasing independence in academic contexts and activities of daily living (ADL). The analysis revealed that TEACCH implementation consistently enhances children’s independence, as indicated by significant improvements in academic task completion (with an average score increase of 34–50 points), as well as improvements in ADL skills such as dressing, eating, and maintaining personal hygiene. The success of this approach is determined by the integration of structural elements, such as environmental organization, the use of visual aids, consistent routines, and collaboration between teachers and parents. This study concludes that TEACCH is an adaptive, effective, and relevant approach for implementation within the Indonesian education system. The novelty of this research lies in its contextual focus on TEACCH application in Indonesia, as well as strategic recommendations for its integration into special education (SLB) and inclusive school curricula through systemic educator capacity-building.